Tüketicilerin alışveriş merkezlerini tercih etme nedenleri ve sadakate etkisi üzerine bir araştırma - (:unkn) unknown (My University, 2009)
Özet: Perakendecilik dünyada ve Türkiye'de hızla büyüyen bir sektör haline gelmiştir. Tüketicilerin yaşam tarzlarındaki değişimlerle birlikte alışveriş merkezlerine olan talepleri artmaya başlamış ve bu talebi karşılamak üzere son on yılda Türkiye'de alışveriş merkezi sayısı hızla artmıştır. Bu büyüme beraberinde yoğun rekabeti de getirmiştir. Bu çalışmanın amacı tüketicilerin alışveriş merkezlerine olan sadakatini etkileyen faktörleri tespit etmektir. Araştırma istanbul şehri, Avrupa yakasında bulunan, en az 10 yıldır faaliyet gösteren ve en fazla ziyaret edilen dört alışveriş merkezi müşterileri üzerine yapılmıştır. Toplam 700 adet geçerli anket analize tabi tutulmuş ve regresyon analizi sonucuna göre tüketicilerin alışveriş merkezine sadakatleri üzerinde etkili olan faktörlerin mağaza özellikleri, kültürel etkinlikler ve eğlence olanakları ve fiyatların uygunluğu ile fiyat/kalite ilişkisi olduğu ortaya çıkmıştır.

Abstract: The retailing industry has become a growing sector in both the world and Turkey. As the life styles of consumers change, their demand for shopping malls has increased and in order to meet this demand the number of shopping malls in Turkey has grown tremendously. In order for shopping malls to be successful, they need to differentiate themselves and also meet the expectations of the consumers. The aim of this study is to determine the factors that affect the loyalty of customers to shopping malls. The research was conducted on customers who visit the four most heavily visited shopping malls that have been operating for at least 10 years in the European side of Istanbul. The total number of usable surveys were 700. According to the regression analysis results, three factors emerged as having an impact on loyalty: characteristics of the retail shops, cultural and entertainment opportunities and appropriate prices as well as price/quality relationship.
A research on the customers' reasons for choosing shopping malls and their effect on loyalty